Quantitative evaluation of swallowing function in Parkinson’s disease using tongue pressure measurement: a mini-review - Fukuoka, Tatsuyuki; Hori, Kazuhiro; Ono, Takahiro (Frontiers in Neurology, 2024)
Dysphagia is a common symptom of Parkinson’s disease (PD) associated with aspiration pneumonia, choking, malnutrition, and a decreased quality of life, and is a leading cause of death among patients with PD. Tongue dysfunction in patients with PD affects the oral phase of swallowing, including the formation and propulsion of a bolus into the pharynx. Assessing tongue pressure, generated between the tongue and palate, is a method that quantitatively measures tongue function and is related to dysphagia in PD. Two assessment methods are used to measure tongue pressure: tongue strength and tongue pressure during swallowing. Previous studies measuring tongue pressure in PD have reported decreased tongue strength and pressure during swallowing, as well as a prolonged tongue pressure rise time, which are symptoms associated with PD severity and dysphagia. In this mini-review, we present a method for measuring tongue pressure and discuss its relationship with dysphagia in PD. We also describe limitations and future perspectives in tongue pressure measurement research.